A molybdenum disulfide / alumina modified foamed carbon-based paraffin phase change energy storage material, a preparation method and application thereof
Patent Information
- Application Number
- CN202611349847.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-09-02
- Publication Date
- 2026-10-13
AI Technical Summary
[0005]本发明的目的在于提供一种二硫化钼/氧化铝改性泡沫炭基石蜡相变储能材料及其制备方法和应用,解决现有相变复合材料导热率低、易泄漏以及填料易团聚等问题
(1)导热性能实现阶跃式提升:本发明通过片层MoS2与球形Al2O3的复配,构建了高效的“点-面”协同导热通路,球形填料完美搭接了片层间的导热死角(微观结构示意图如图1所示)。这一结构设计成功将基础“泡沫炭+石蜡”体系的导热系数从0.12 W/(m·K)显著提升至0.22 W/(m·K),大幅加快了热量在相变体系中的传导速率。
Smart Images

Figure CN122898255A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of phase change thermal energy storage materials, and in particular to a molybdenum disulfide / alumina modified foamed carbon-based paraffin phase change energy storage material, its preparation method, and its application. Background Technology
[0002] With the rapid development of the global economy and the accelerated iteration of electronic information technology, electronic devices are evolving towards higher integration and higher power density, leading to a sharp increase in localized heat generated during device operation. Thermal energy storage and management technology, as a key means to solve the heat dissipation problem of electronic devices and achieve energy supply and demand balance, plays an extremely important role. Phase change thermal storage materials (PCMs), capable of absorbing or releasing large amounts of latent heat at constant temperatures, are currently a research focus in the field of thermal management.
[0003] Paraffin wax, as the most commonly used organic phase change material, has advantages such as high heat storage density, stable chemical properties, and low cost. However, pure paraffin wax generally suffers from two major fatal defects in practical applications: first, its intrinsic thermal conductivity is extremely low, and the heat transfer rate inside the material is slow, which severely limits its heat storage and release rate; second, liquid leakage is very likely to occur during the solid-liquid phase change process, affecting the operational safety and service life of equipment.
[0004] To overcome the aforementioned shortcomings, porous matrices (such as carbon foam) are typically used to physically encapsulate paraffin. However, while conventional carbon foam + paraffin composites solve the leakage problem, their overall thermal conductivity remains extremely low (typically only around 0.12 W / (m·K), failing to meet the rapid heat dissipation requirements of high-power devices. Therefore, introducing highly thermally conductive inorganic fillers into the system has become an effective approach. However, thermally conductive fillers with a single morphology tend to agglomerate in organic matrices, and the contact thermal resistance between fillers is high, making it difficult to form continuous and efficient thermal conduction pathways. How to construct an efficient synergistic thermal conduction network within a phase change system through the rational design of thermally conductive filler morphology blends and surface modification is a pressing technical challenge in this field. Summary of the Invention
[0005] The purpose of this invention is to provide a molybdenum disulfide / alumina modified foamed carbon-based paraffin phase change energy storage material, its preparation method and application, to solve the problems of low thermal conductivity, easy leakage and easy agglomeration of existing phase change composite materials.
[0006] To achieve the above-mentioned objectives, the present invention provides the following technical solution: This invention provides a method for preparing a molybdenum disulfide / alumina modified foamed carbon-based paraffin phase change energy storage material, comprising the following steps: (1) Add silane coupling agent to ethanol aqueous solution to obtain modified solution; add lamellar molybdenum disulfide (MoS2) and spherical alumina (Al2O3) to modified solution and react to obtain surface modified thermally conductive filler. (2) The surface-modified thermally conductive filler is melt-mixed with paraffin to obtain a modified paraffin phase change material; (3) The foamed carbon is immersed in molten modified paraffin phase change material and vacuum melt impregnation is performed to obtain a preform; (4) The preform is mechanically flattened, and then water-based polyurethane (WPU) is coated on the surface and cured to obtain molybdenum disulfide / alumina modified foam carbon-based paraffin phase change energy storage material.
[0007] Preferably, the silane coupling agent is KH570; the mass of the silane coupling agent is 5-10% of the total mass of the lamellar molybdenum disulfide and spherical alumina.
[0008] Preferably, the lamellar molybdenum disulfide has a size of 6-8 μm; and the spherical alumina has a particle size of 1-10 μm.
[0009] Preferably, the mass ratio of the lamellar molybdenum disulfide to the spherical alumina is 1:1 to 1:10.
[0010] Preferably, the reaction temperature is 55~75 °C and the time is 3~5 h.
[0011] Preferably, the mass ratio of the surface-modified thermally conductive filler to paraffin is 1:8 to 1:10.
[0012] Preferably, the melting temperature is 90 °C; and the vacuum melting impregnation time is 2-4 h.
[0013] Preferably, the mechanical flattening pressure is 10 MPa, the temperature is 25 ℃, and the time is 20~30 min; the thickness of the waterborne polyurethane coating is 1~3 mm.
[0014] The present invention also provides a molybdenum disulfide / alumina modified foamed carbon-based paraffin phase change energy storage material prepared by the above preparation method.
[0015] The present invention also provides a molybdenum disulfide / alumina modified foamed carbon-based paraffin phase change energy storage material prepared by the above preparation method, or the application of the above molybdenum disulfide / alumina modified foamed carbon-based paraffin phase change energy storage material in battery thermal management, electronic device heat dissipation, or building energy-saving insulation.
[0016] As can be seen from the above technical solution, compared with the prior art, the present invention has the following beneficial effects: (1) A significant improvement in thermal conductivity: This invention constructs a highly efficient "point-to-surface" synergistic thermal conductivity pathway by combining sheet-like MoS2 with spherical Al2O3. The spherical filler perfectly fills the thermal conductivity dead zones between the sheets (microscopic structure diagram as shown in the figure). Figure 1 (As shown). This structural design successfully increased the thermal conductivity of the basic "foamed carbon + paraffin" system from 0.12 W / (m·K) to 0.22 W / (m·K), significantly accelerating the heat transfer rate in the phase change system.
[0017] (2) Excellent leakage prevention and shape stability: The present invention completely solves the leakage problem of paraffin in the solid-liquid phase change process by adopting the dual encapsulation strategy of "porous foam carbon confinement + surface WPU coating and curing". After repeated heating and cooling, the mass loss is minimal, showing excellent thermal reliability.
[0018] (3) Combining flexibility and low contact thermal resistance: The combination of flattening process and flexible WPU coating breaks the rigid and brittle fracture limitation of traditional foam carbon materials, enabling them to closely fit various complex heat sources (such as battery surface, chip, etc.), thereby further reducing the interface contact thermal resistance on a macroscopic level. Attached Figure Description
[0019] To more clearly illustrate the technical solutions in the embodiments of the present invention or the prior art, the drawings used in the description of the embodiments or the prior art will be briefly introduced below.
[0020] Figure 1 This is a schematic diagram of the microstructure of the molybdenum disulfide / alumina modified foamed carbon-based paraffin phase change energy storage material of the present invention. Figure 2 This is a schematic diagram of the preparation process of the molybdenum disulfide / alumina modified foamed carbon-based paraffin phase change energy storage material of the present invention. Detailed Implementation
[0021] This invention provides a method for preparing a molybdenum disulfide / alumina modified foamed carbon-based paraffin phase change energy storage material, the process flow diagram of which is shown below. Figure 2 As shown, it includes the following steps: (1) Add silane coupling agent to an aqueous ethanol solution to obtain a modified solution; add lamellar molybdenum disulfide and spherical alumina to the modified solution and react to obtain a surface-modified thermally conductive filler. (2) The surface-modified thermally conductive filler is melt-mixed with paraffin to obtain a modified paraffin phase change material; (3) The foamed carbon is immersed in molten modified paraffin phase change material and vacuum melt impregnation is performed to obtain a preform; (4) The preform is mechanically flattened, and then water-based polyurethane is coated on the surface and cured to obtain molybdenum disulfide / alumina modified foam carbon-based paraffin phase change energy storage material.
[0022] In this invention, the aqueous ethanol solution is preferably composed of anhydrous ethanol and water in a volume ratio of 95:5.
[0023] In this invention, the silane coupling agent is preferably KH570; the mass of the silane coupling agent is preferably 5-10% of the total mass of lamellar molybdenum disulfide and spherical alumina, and more preferably 7-9%.
[0024] In this invention, the preferred ratio of the silane coupling agent to the aqueous ethanol solution is 0.5~1 g:100 mL, and more preferably 0.6~0.8 g:100 mL.
[0025] In this invention, the size of the lamellar molybdenum disulfide is preferably 6-8 μm, and it is derived from the Titan Technology Exploration Platform.
[0026] In this invention, the particle size of the spherical alumina is preferably 1~10 μm, and more preferably 1 μm, 5 μm or 10 μm.
[0027] In this invention, the mass ratio of the lamellar molybdenum disulfide to the spherical alumina is preferably 1:1 to 1:10, and more preferably 1:5 to 1:7.
[0028] In this invention, the reaction temperature is preferably 55~75 ℃, more preferably 60~70 ℃, and the reaction time is preferably 3~5 h, more preferably 4~5 h.
[0029] In this invention, the mass ratio of the surface-modified thermally conductive filler to paraffin is preferably 1:8 to 1:10, and more preferably 1:9 to 1:10.
[0030] In this invention, the melting temperature is preferably 90 °C; the vacuum melting and impregnation time is preferably 2-4 h, more preferably 2-3 h.
[0031] In this invention, the porosity of the foamed carbon is preferably 70%; the foamed carbon also includes ultrasonic cleaning and drying before use.
[0032] In this invention, the mechanical flattening pressure is preferably 10 MPa, the temperature is preferably 25 ℃, and the time is preferably 20~30 min, more preferably 25~30 min.
[0033] In this invention, the thickness of the waterborne polyurethane coating is preferably 1-3 mm, and more preferably 2-3 mm.
[0034] In this invention, the waterborne polyurethane is sourced from Foshan Shunde Sansheng Trading Co., Ltd., specifically PU-3777 waterborne polyurethane.
[0035] In this invention, the curing temperature is preferably 45 ℃, and the curing time is preferably 1~3 h, more preferably 2~3 h.
[0036] The present invention also provides a molybdenum disulfide / alumina modified foamed carbon-based paraffin phase change energy storage material prepared by the above preparation method.
[0037] The present invention also provides a molybdenum disulfide / alumina modified foamed carbon-based paraffin phase change energy storage material prepared by the above preparation method, or the application of the above molybdenum disulfide / alumina modified foamed carbon-based paraffin phase change energy storage material in battery thermal management, electronic device heat dissipation, or building energy-saving insulation.
[0038] The technical solutions in the embodiments of the present invention will be clearly and completely described below. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.
[0039] Example 1
[0040] S1. Pretreatment of foamed carbon: Immerse commercially available foamed carbon (10 cm × 10 cm, porosity 70%, pore size 100~300 μm) in anhydrous ethanol, ultrasonically clean for 15 min, remove and dry in an 80 ℃ oven for later use.
[0041] S2. Surface Modification of Thermally Conductive Filler: A beaker containing 95 mL of anhydrous ethanol and 5 mL of deionized water was added, along with 0.8 g of KH570 silane coupling agent. The mixture was mechanically stirred for 0.5 h. 10 g of thermally conductive filler was added, wherein the mass ratio of lamellar MoS2 (6–8 μm in size) to spherical Al2O3 (1 μm in particle size) was 1:1. The system was heated to 65 °C and continuously stirred for 4 h. The solid phase was separated by centrifugation and dried in an oven for 12 h to obtain the surface-modified thermally conductive filler.
[0042] S3. Preparation of composite phase change matrix: Mix surface-modified thermally conductive filler with solid paraffin at a mass ratio of 1:9, melt in a 90 ℃ oven, and stir to disperse evenly to obtain modified paraffin.
[0043] S4. Vacuum Impregnation: Keep the modified paraffin wax in a molten state, immerse the pretreated foamed carbon in it, and perform vacuum melt impregnation at 90 ℃ and -0.1 MPa for 2 h in a vacuum drying oven. After removal, wipe off the excess modified paraffin wax from the surface of the foamed carbon.
[0044] S5. Flattening and Coating Encapsulation: Place the sample between two flat steel plates and flatten it at a pressure of 10 MPa, a temperature of 25 ℃, and a time of 30 min. Then, uniformly coat the front and back surfaces with water-based polyurethane and let it stand at 45 ℃ for 3 h to cure into a film with a thickness of 1 mm, thus obtaining the composite material.
[0045] Example 2
[0046] The preparation process is similar to that in Example 1. The difference is that the thermally conductive filler added in step S2 has a mass ratio of lamellar MoS2 to spherical Al2O3 of 1:3. The remaining steps remain unchanged.
[0047] Example 3
[0048] The preparation process is similar to that in Example 1. The difference is that the thermally conductive filler added in step S2 has a mass ratio of lamellar MoS2 to spherical Al2O3 of 1:5. The remaining steps remain unchanged.
[0049] Example 4
[0050] The preparation process is similar to that in Example 1. The difference is that the thermally conductive filler added in step S2 has a mass ratio of lamellar MoS2 to spherical Al2O3 of 1:7. The remaining steps remain unchanged.
[0051] Example 5
[0052] The preparation process is similar to that in Example 1. The difference is that the thermally conductive filler added in step S2 has a mass ratio of lamellar MoS2 to spherical Al2O3 of 1:10. The remaining steps remain unchanged.
[0053] Comparative Example 1
[0054] The preparation process is similar to that of Example 1. The difference is that no thermally conductive filler (i.e., pure foamed carbon + paraffin system) is added in steps S2 and S3. The pretreated foamed carbon is directly immersed in pure paraffin at 90 °C for vacuum impregnation, then removed, flattened, and coated with WPU. This is used to compare the effect of the thermally conductive filler network on improving thermal conductivity.
[0055] Comparative Example 2
[0056] The preparation process is similar to that in Example 4. The difference is that KH570 coupling agent is not added in step S2; instead, sheet-like MoS2 and spherical Al2O3 (1:7) are directly added to paraffin and mixed. This is used to compare the effect of surface modification on improving filler dispersion and reducing interfacial thermal resistance.
[0057] Comparative Example 3
[0058] The preparation process is similar to that in Example 4. The difference is that the thermally conductive filler added in step S2 is only lamellar MoS2.
[0059] Comparative Example 4
[0060] The preparation process is similar to that in Example 4. The difference is that the thermally conductive filler added in step S2 is only spherical Al2O3.
[0061] Performance testing
[0062] The composite materials obtained in Examples 1-5 and Comparative Examples 1-2 were subjected to performance tests. Thermal conductivity was measured using a Lindsay TIM-Tester (TIM L58) thermal interface material tester, following the ASTM D5470 standard. Circular samples with a diameter of 25 mm were used, and the test was repeated three times, with the average value taken. The latent heat of phase change was measured using a differential scanning calorimeter (METTLER TOLEDO), with a test temperature ranging from 0 to 100 °C and a heating rate of 10 °C / min, under nitrogen protection. For thermal cycling stability testing, the materials were weighed, placed on a heating platform, heated from room temperature to 80 °C, and then naturally cooled to room temperature. This process was repeated 20 times, followed by weighing. The test results are shown in Table 1.
[0063] Table 1 Performance test results of phase change thermal storage composite materials
[0064] As shown in Table 1, the thermal conductivity of Comparative Example 1 (pure foamed carbon + paraffin) without thermally conductive filler is only 0.127 W / (m·K); the thermal conductivity of Comparative Example 3 with only lamellar MoS2 or Comparative Example 4 with only spherical Al2O3 is only 0.129 W / (m·K) and 0.135 W / (m·K), respectively; while in Example 4, by introducing lamellar MoS2 and spherical Al2O3 in a 1:7 ratio, the spherical particles were successfully embedded in the gaps between the lamellars, increasing the thermal conductivity pathway and causing the thermal conductivity of the composite material to jump to 0.22 W / (m·K), with increases of 73.2%, 70.5%, and 63%, respectively.
[0065] As shown in Comparative Examples 1 and 2 and Example 4, the optimal synergistic effect of the lamellar and spherical filler is achieved when the ratio of lamellar to spherical filler is 1:7. However, in Comparative Example 2, due to the lack of KH570 modification, the poor compatibility between the inorganic filler and paraffin led to agglomeration, resulting in a thermal conductivity increase of only 0.152 W / (m·K). This demonstrates that surface modification is crucial for constructing a highly efficient thermally conductive network.
[0066] Furthermore, all examples and comparative examples using the "flattening + WPU coating" process showed no significant leakage after baking at 80 °C (above the melting point of paraffin) for 2 hours, with a mass loss rate of less than 0.5%, demonstrating extremely excellent leak-proof performance and meeting the demanding application requirements in fields such as electronic devices and battery thermal management.
[0067] The above description is only a preferred embodiment of the present invention. It should be noted that for those skilled in the art, several improvements and modifications can be made without departing from the principle of the present invention, and these improvements and modifications should also be considered within the scope of protection of the present invention.
Claims
1. A method for preparing a molybdenum disulfide / alumina modified foamed carbon-based paraffin phase change energy storage material, characterized in that, Includes the following steps: (1) Add the silane coupling agent to an aqueous ethanol solution to obtain the modified solution; Lamellar molybdenum disulfide and spherical alumina are added to the modification solution and reacted to obtain a surface-modified thermally conductive filler. (2) The surface-modified thermally conductive filler is melt-mixed with paraffin to obtain a modified paraffin phase change material; (3) The foamed carbon is immersed in molten modified paraffin phase change material and vacuum melt impregnation is performed to obtain a preform; (4) The preform is mechanically flattened, and then water-based polyurethane is coated on the surface and cured to obtain molybdenum disulfide / alumina modified foam carbon-based paraffin phase change energy storage material.
2. The preparation method according to claim 1, characterized in that, The silane coupling agent is KH570; the mass of the silane coupling agent is 5-10% of the total mass of lamellar molybdenum disulfide and spherical alumina.
3. The preparation method according to claim 1, characterized in that, The lamellar molybdenum disulfide has a size of 6-8 μm; the spherical alumina has a particle size of 1-10 μm.
4. The preparation method according to claim 1, characterized in that, The mass ratio of the lamellar molybdenum disulfide to the spherical alumina is 1:1 to 1:
10.
5. The preparation method according to claim 1, characterized in that, The reaction is carried out at a temperature of 55-75 °C for 3-5 h.
6. The preparation method according to claim 1, characterized in that, The mass ratio of the surface-modified thermally conductive filler to paraffin is 1:8 to 1:
10.
7. The preparation method according to claim 1, characterized in that, The melting temperature is 90 °C; the vacuum melting and impregnation time is 2-4 h.
8. The preparation method according to claim 1, characterized in that, The mechanical flattening pressure is 10 MPa, the temperature is 25 ℃, and the time is 20~30 min; the thickness of the water-based polyurethane coating is 1~3 mm.
9. A molybdenum disulfide / alumina modified foamed carbon-based paraffin phase change energy storage material prepared by the preparation method according to any one of claims 1 to 8.
10. The application of a molybdenum disulfide / alumina modified foamed carbon-based paraffin phase change energy storage material prepared by the preparation method according to any one of claims 1 to 8, or the molybdenum disulfide / alumina modified foamed carbon-based paraffin phase change energy storage material according to claim 9, in battery thermal management, electronic device heat dissipation, or building energy-saving insulation.